PENINGKATAN KEMAMPUAN MENGGUNAKAN MICROSOFT POWER POINT SEBAGAI MEDIA PEMBELAJARAN BAGI GURU PENDIDIKAN KHUSUS MELALUI KEGIATAN PELATIHAN DENGAN METODE TUTOR SEBAYA DI GUGUS 11 KOTA TANGERANG ( - Teuteu Nurbayan (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2019)
Abstract, The use of learning media by utilizing the Microsoft Powerpoint application program is done by packaging teaching material in an interesting, concise, dense and effective manner. In accordance with the demands of the teacher's professionalism in educating, the ability of each teacher to develop ICT-based teaching materials is absolutely necessary. But not infrequently there are still teachers who until now have not understood and are not so familiar with the use of ICT-based teaching materials. One effort to overcome the teacher's inability to use computers and access the internet in order to create learning media is to use peer tutoring methods in the training activities held in Cluster 11 Tangerang City. Through this peer tutor, the teacher is not only used as a learning object but is the subject of learning, where the teacher is invited to become a tutor or learning resource and becomes a place to ask his friends. This study uses action research as many as two rounds of silk. Each round consists of four stages, namely: planning, conducting activities and observing, and reflecting. The target of this study was 20 special education teachers in Tangerang City Cluster. Data is obtained from the results of questionnaires and written knowledge tests. From the questionnaire calculation the value data obtained before the action reached 15% then rose to 60% in the first cycle and continued to increase to 100% in the second cycle. Based on the results of the written knowledge test from before the action and the second cycle cycle obtained an increase in the average value of 48.75 before the action then rose to 79.25 in the first cycle and continued to increase to 84.25 in Cycle II. From these data it can be concluded that training with peer tutoring methods can improve the ability to use the Microsoft Power Point program as a learning medium for special education teachers in Cluster 11 Tangerang City.